2017
DOI: 10.3748/wjg.v23.i17.3053
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7/CXCL12 axis is involved in lymph node and liver metastasis of gastric carcinoma

Abstract: AIMTo investigate the role of CXC chemokine receptor (CXCR)-7 and CXCL12 in lymph node and liver metastasis of gastric carcinoma.METHODSIn 160 cases of gastric cancer, the expression of CXCR7 and CXCL12 in tumor and matched tumor-adjacent non-cancer tissues, in the lymph nodes around the stomach and in the liver was detected using immunohistochemistry to analyze the relationship between CXCR7/CXCL12 expression and clinicopathological features and to determine whether CXCR7 and CXCL12 constitute a biological ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Among 27 studies, three studies each evaluated colorectal carcinoma (or rectal cancer) 18 - 20 , hepatocellular carcinoma 21 - 23 , esophageal carcinoma (or esophageal squamous cell carcinoma) 13 , 24 , 25 , and thyroid carcinoma 26 - 28 . Two studies evaluated renal cell carcinoma 29 , 30 , pancreatic cancer 31 , 32 , cervical cancer (or cervical squamous cell carcinoma) 33 , 34 , nasopharyngeal carcinoma 35 , 36 , glioma or glioblastoma 37 , 38 and gastric cancer 39 , 40 . One study evaluated gallbladder cancer 14 , cutaneous squamous cell carcinoma 41 and chondrosarcoma 42 .…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Among 27 studies, three studies each evaluated colorectal carcinoma (or rectal cancer) 18 - 20 , hepatocellular carcinoma 21 - 23 , esophageal carcinoma (or esophageal squamous cell carcinoma) 13 , 24 , 25 , and thyroid carcinoma 26 - 28 . Two studies evaluated renal cell carcinoma 29 , 30 , pancreatic cancer 31 , 32 , cervical cancer (or cervical squamous cell carcinoma) 33 , 34 , nasopharyngeal carcinoma 35 , 36 , glioma or glioblastoma 37 , 38 and gastric cancer 39 , 40 . One study evaluated gallbladder cancer 14 , cutaneous squamous cell carcinoma 41 and chondrosarcoma 42 .…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…CXCR7, also known as RDC1, is one of the CXCR subtype cytokines. The activation of CXCR7 by its ligand CXCL12 could promote cell migration, angiogenesis, tumorigenesis, invasion, metastasis and anti-apoptosis [25]. CXCR7 is considered to be an EMT-related gene and is highly expressed in various cancer cells [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The NAGLU gene was found to be low‐methylated and in negative correlation to HCC stage by comparing T2D with ND and HCC with the control group (Figure d–f). It was shown that processing of CXCL12 impedes the recruitment of endothelial progenitor cells in diabetic wound healing (Feng et al, ), CXCL12 axis is involved in lymph node and liver metastasis of gastric carcinoma (Xin et al, ). DDX5 and KL genes were found to be low‐methylated and in positive correlation with HCC stage by comparing T2D with ND and HCC with the control group (Figure g,h).…”
Section: Resultsmentioning
confidence: 99%